2015
DOI: 10.1021/acschembio.5b00628
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a New Type of Covalent PPARγ Agonist using a Ligand-Linking Strategy

Abstract: Peroxisome proliferator-activated receptor γ (PPARγ) is a ligand-activated transcription factor that plays an important role in adipogenesis and glucose metabolism. The ligand-binding pocket (LBP) of PPARγ has a large Y-shaped cavity with multiple subpockets where multiple ligands can simultaneously bind and cooperatively activate PPARγ. Focusing on this unique property of the PPARγ LBP, we describe a novel two-step cell-based strategy to develop PPARγ ligands. First, a combination of ligands that cooperativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…A recent study demonstrated that attaching a large lipophilic moiety to GW9662, which can occupy more space in the large orthosteric pocket, can convert the orthosteric covalent antagonist scaffold into a covalent agonist that activates PPARγ transcription. 38 Another study expanded the orthosteric covalent antagonist scaffold into the allosteric site to demonstrate that occupancy of the allosteric site can block phosphorylation of PPARγ. 21 Here, we desired to develop a covalent dual-site PPARγ antagonist that induces no or low transcriptional activation on its own and inhibits both orthosteric and allosteric activation by other PPARγ-binding ligands.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study demonstrated that attaching a large lipophilic moiety to GW9662, which can occupy more space in the large orthosteric pocket, can convert the orthosteric covalent antagonist scaffold into a covalent agonist that activates PPARγ transcription. 38 Another study expanded the orthosteric covalent antagonist scaffold into the allosteric site to demonstrate that occupancy of the allosteric site can block phosphorylation of PPARγ. 21 Here, we desired to develop a covalent dual-site PPARγ antagonist that induces no or low transcriptional activation on its own and inhibits both orthosteric and allosteric activation by other PPARγ-binding ligands.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, molecular simulation evidence could also explain why GW9662 antagonized ligustrazine effects. It has been delineated that GW9662 covalently reacted with the Cys285 residue in the PPARγ ligand-binding domain, which is closely adjacent to the Ser289 residue 42 . Accordingly, we speculated that GW9662 could competitively interrupt the formation of hydrogen bonds between the pyrazine nitrogen of ligustrazine and the Ser289 residue in the active cavity of PPARγ, resulting in the loss of ligustrazine suppression of HSC pericyte functions.…”
Section: Discussionmentioning
confidence: 99%
“…Here we clearly demonstrate that the binding to PPARγ is strictly dependent on this cysteine residue at position 285, as a site-directed mutation impairs the transactivation ability (Figs 3 and 5). This residue has been shown to be essential for the activity and covalent binding of some PPARγ agonists such as 15d-PGJ 2 25, indicating that the same amino acid residue may be crucial to the binding of both full and partial agonists5051. Further investigations are necessary to clarify this aspect.…”
Section: Discussionmentioning
confidence: 99%